2012
DOI: 10.1111/j.1365-2184.2011.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

A new development of triterpene acid‐containing extracts from Viscum album L. displays synergistic induction of apoptosis in acute lymphoblastic leukaemia

Abstract: Here for the first time, we have demonstrated that either solubilized triterpene acids or lectins and combinations thereof, induce dose-dependent apoptosis in the ALL cell line NALM-6 via caspase-8 and -9 dependent pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 62 publications
2
58
0
1
Order By: Relevance
“…22,25,26 In vitro studies have shown induction of apoptosis and necrosis depending on mistletoe extract concentrations in a wide range of tumor cells. [19][20][21]25,27,28 Preclinical in vivo studies have likewise been promising, with IT injection of tumors in a range of mice models and in horses inhibiting tumor growth and inducing partial or complete regressions. 25,26,28,29 As for clinical use, several groups have published case studies describing partial or complete tumor remission by IT mistletoe therapy alone or in combination with conventional therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,25,26 In vitro studies have shown induction of apoptosis and necrosis depending on mistletoe extract concentrations in a wide range of tumor cells. [19][20][21]25,27,28 Preclinical in vivo studies have likewise been promising, with IT injection of tumors in a range of mice models and in horses inhibiting tumor growth and inducing partial or complete regressions. 25,26,28,29 As for clinical use, several groups have published case studies describing partial or complete tumor remission by IT mistletoe therapy alone or in combination with conventional therapies.…”
Section: Introductionmentioning
confidence: 99%
“…10,[13][14][15][16][17] A major challenge of cancer therapy is immune resistance orchestrated by the tumor microenvironment, which promotes tumor survival. 18 European mistletoe (Viscum album [19][20][21][22] Used in anticancer therapy in central Europe since 1917, anthroposophic mistletoe preparations (ie, Abnoba viscum, Helixor, Iscador, Iscucin, Isorel) are usually injected subcutaneously (SC), as an adjuvant therapy to conventional cancer treatments. The aims of SC-injected mistletoe (also intravenous [IV]), are to boost the immune system, improve patient health-related quality of life, and reduce ADRs associated with conventional therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In German-speaking countries, there is a high prevalence of complementary and alternative medicine, 41,42 and European mistletoe extracts (Viscum album L.) are the mostly frequently prescribed herbal remedies. [43][44][45][46][47][48] An overview on the mode of action of mistletoe extracts is given by Bar-Sela 49 and has been well summarized by Zänker et al 50 In vitro, it showed antitumoral effects, such as induction of apoptosis, [44][45][46][47][48]51 inhibition of cell proliferation, 47,48,52 potentiating anticancer effects of TNF-alpha, 53,54 activation of immunocompetent cells, [54][55][56][57] decreasing angiogenesis, 50,53 and retention of chemotherapeutic agents in cancer cells by modulating the transport of cell-toxifying substances. 58 Whereas systemic mistletoe therapy primary aims to stimulate the immune system, intratumoral application focuses on the local cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mistletoe is grown on different host trees such apple, pine, oak, fur, maple, poplar, or hawthorn. 23 In Europe, mistletoe lectin has been widely used as a complementary cancer drug for various cancers, such as gliomas, 24 acute lymphoblastic leukemia, 25 breast cancer, 26 sarcoma, 27 and others. 28 However, there has been no study showing the anticancer activity of mistletoe alkali.…”
Section: Ge Effects Of Mistletoe Alkali On Human Osteosarcoma Cells (mentioning
confidence: 99%